Proses Pengambilan Keputusan Bantuan Beasiswa SEHATI di Yayasan Senyum Kita dengan Metode DEMATEL dan F-AHP - Syahruni, Aenun; Kurniawan, V. Reza Bayu; Ma’arif, Syamsul (Go-Integratif : Jurnal Teknik Sistem dan Industri, 2024)
The decision-making process for selecting recipients of the SEHATI Scholarship by the Yayasan Senyum Kita frequently faces challenges in ensuring transparency and fairness. This study aims to enhance the decision-making system by applying the DEMATEL (Decision Making Trial and Evaluation Laboratory) and F-AHP (Fuzzy Analytic Hierarchy Process) methods. The research involved 20 children for the 2023/2024 academic year during the odd semester, examining three main criteria: parental income (K1), orphan status (K2), and disability (K3). Results from both methods indicated that the K2 criterion dominates the selection process. The DEMATEL analysis revealed that K2 has the most significant influence on decision-making, while F-AHP confirmed this influence by assigning it the highest weight of 0.37 out of 1.00. Furthermore, both methods suggested a nearly identical number of qualified children, with DEMATEL identifying 11 and F-AHP 10. The application of DEMATEL and F-AHP successfully increased transparency and objectivity in the selection process and recommended a more systematic framework for evaluating scholarship eligibility.